An Analysis of Toxicity of Artificial Sweeteners - John Abraham; John Abraham; Gurshan Singh Gill; Asit Kumar; Y. C. Tripathi (International Journal of Pharma and Bio Sciences, 2024)
Monosaccharides and disaccharides, natural sweeteners, have some nutritional value, but artificial sweeteners have few or absence of nutritional advantages. The influence of sugar on health is a subject of debate, especially in light of increasing apprehensions over diabetes and obesity. In the 21st century, a growing number of individuals opt for low-calorie, artificially sweetened items to control their weight and blood glucose levels due to increasing health awareness. Although widely used, artificial sweeteners are controversial because of their safety and effectiveness concerns. According to reports, these medications may have adverse effects such as headaches, weight gain, and organ malfunction, which raises concerns about their prolonged usage. Conversely, sweeteners derived from natural sources, such as stevia, are seen as being more secure. While the FDA has approved some artificial sweeteners, there is still ongoing dispute regarding their metabolic consequences. Hence, customers had to select between synthetic and organic sweeteners meticulously. The early published reviews of the "Artificial Sweeteners" were deficient in extensive long-term human investigations, mainly depended on animal research, neglected to analyze different types of sweeteners, and disregarded confounding factors such as food and lifestyle. This review aims to acquire information regarding the various types of available sweeteners, their composition, their impact on human health, and a thorough comparison between natural and artificial sweeteners. This review aims to assist readers in developing a healthy diet plan and making informed choices when using products that contain sweeteners.